Factors determining variation in colour morph frequencies in invasive Harmonia axyridis populations - Honek, Alois; Brown, Peter M. J.; Martinkova, Zdenka; Skuhrovec, Jiri; Brabec, Marek; Burgio, Giovanni; Evans, Edward W.; Fournier, Marc; Grez, Audrey A.; Kulfan, Jan; Lami, Francesco; Lucas, Eric; et al. (Biological invasions, 2020)
The Harlequin ladybird Harmonia axyridis Pallas, native to eastern Asia, is an invasive, non-native species that has recently achieved an almost worldwide distribution. A conspicuous feature of this species is colour polymorphism of the elytra. In its native area, the populations consist of a recessive non-melanic morph, several dominant melanic morphs and small numbers of other (rare) morphs. The morph proportions in native populations have been intensively studied and vary with geographic area, climate and time. In contrast, colour polymorphism in invaded regions has been little studied. We examine and try to account for the morph frequencies observed across the different invaded regions. In America, monomorphic populations consist of the non-melanic morphs while European populations contain also melanic morphs. In particular geographic areas of Europe, the average percentage of the non-melanic morphs varied between 78 and 99%. It was highest in the lowlands of northern Italy and central and northern Europe and decreased in the Alps and western (Spain, UK) and eastern (southeast Russia) margins of the recently invaded area. In central Europe the frequency of the non-melanic morphs decreased over the course of the year but increased over the years from 2010 to 2018. The local differences might thus arise through gradual change of the morph composition of the founder invasive, non-native population. However, the variation in non-melanic morph frequency was not correlated with climatic characteristics that might affect coccinellid polymorphism. The observed rate of change in morph proportions in our data was too small to explain the diversification of what was supposedly a uniform invasive, non-native population at the point of introduction.